Membrane-Associated Heat Shock Proteins in Oncology: From Basic Research to New Theranostic Targets - Maxim Shevtsov; Zsolt Balogi; William Khachatryan; Huile Gao; László Vígh; Gabriele Multhoff (Cells, 2020)
Heat shock proteins (HSPs) constitute a large family of conserved proteins acting as molecular chaperones that play a key role in intracellular protein homeostasis, regulation of apoptosis, and protection from various stress factors (including hypoxia, thermal stress, oxidative stress). Apart from their intracellular localization, members of different HSP families such as small HSPs, HSP40, HSP60, HSP70 and HSP90 have been found to be localized on the plasma membrane of malignantly transformed cells. In the current article, the role of membrane-associated molecular chaperones in normal and tumor cells is comprehensively reviewed with implications of these proteins as plausible targets for cancer therapy and diagnostics.